Effect of the eQuality Health Bwindi Scheme on Utilization of Health Services at Bwindi Community Hospital in Uganda - Doreen Birungi Agasha; Birungi Mutahunga R. Edwin; Sebastian Olikira Baine (Frontiers Media S.A., 2019)
Introduction: eQuality Health Bwindi (eQHB), a Community Based Health Insurance (CBHI) scheme was launched in March 2010 with the aim of generating income to maintain high quality care as well as increasing access to and utilization of health services at Bwindi Community Hospital (BCH). The main objective of this study was to explore evidence showing that eQHB scheme affected access and utilization of health services at BCH. The evidence generated would be used to inform decision making, policy and scale up of the scheme.Methods and Materials: This study applied qualitative and quantitative research methods. It involved a review of hospital records for the period July 2009-June 2014, a survey of 272 households, four focus group discussions, and six key informant interviews. Both quantitative and qualitative analysis techniques were applied for the analysis.Results: Outpatient attendance, inpatient admissions, and deliveries at the hospital increased by 65, 73, and 27%, respectively between FY 2009/10 and FY 2012/13. Utilization of health services by sick children from insured participants was greater than that of the uninsured members of the community (p-value = 0.0038). BCH services became more affordable. However, opting out of the scheme at a later stage in the review period was attributed to rising unaffordable premiums and co-payments. Failure to afford scheme membership, residing far from BCH and limited understanding of health insurance led to reduced BCH service utilization.Conclusions: eQHB has potential to increase access and utilization of health services at BCH. The challenges are; limited understanding of the concept of health insurance and unaffordable premiums and co-payments set to enable provision of high quality services.Recommendations: Based on these findings, intensified community sensitization on health insurance, establishment of satellite health facilities by BCH to bring services closer to members and transformation of eQHB to a savings/credit society in order to grow savings and subsequently reduce premiums are recommended. Government of Uganda should engage CBHIs countrywide to discuss achievement of UHC and establishment of a national health insurance scheme. A further study to guide setting of affordable premiums and copayments for eQHB is also recommended.